Analisis Kadar Logam Berat Timbal (Pb), Kadmium (Cd), dan Merkuri (Hg) pada Sayuran Selada (Lactuca Satiya L.) yang Beredar di Pasar Sentral Kota Gorontalo - Merlin Darise; Ishak Isa; Mardjan Paputungan; Netty Ino Ischak; Erni Mohamad; Nita Suleman (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
The purpose of this study was to determine the results of the analysis of heavy metal levels of Pb, Cd, Hg found in lettuce in the Central market of Gorontalo city. In this study, the object of research was the roots, stems and leaves of lettuce. The method used was wet deconstruction method using a mixture of HNO3 and HCl. After that the solution was cooled, then filtered. The sample solution that has been deconstructed is analysed by UV-Vis Spectrophotometry. The results of the analysis showed that there was heavy metal Pb in the root, stem and leaf lettuce samples of 2.54 mg / kg, 1.58 mg / kg, 2.28 mg / kg / respectively. Cd heavy metal levels of 0.07 mg/kg, 0.60 mg/kg, 0.65 mg/kg. Hg heavy metal levels of 2.09 mg/kg, 0.21 mg/kg, 0.44 mg/kg. Based on the 2018 Food and Drug Administration regulations, the value of Pb metal content is 0.20 mg/kg, the value of Cd content is 0.05 mg/kg, and the value of Hg content is 0.03 mg/kg.